Improving Learning Achievement in Pancasila Education Through Leker Gamification at the Junior High School Level - Yulia Nur Widiana; Didik Sukriono; Wahyu Nur Rochmadi; Siti Awaliyah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to improve students' learning achievement in Pancasila Education through the application of Leker's Gamification. This research was conducted in class VII-B of SMP Negeri 2 Ponorogo using a Classroom Action Research (CAR) method. The research subjects consisted of 32 students in class VII-B. The study began with a pre-test, followed by two cycles of classroom action research. The first cycle utilized conventional written student worksheets (LKPD), while the second cycle implemented Leker's Gamification, a game-based leveled student worksheet delivered through the Wordwall web platform. Prior to the intervention, students' learning achievement was only 40% mastery. After the first cycle, achievement increased to 59%. In the second cycle, a significant improvement was observed, reaching 93% mastery, surpassing the 90% success indicator. These results demonstrate that the use of Leker's Gamification in learning is effective in significantly improving the learning achievement of class VII-B students at SMP Negeri 2 Ponorogo in the Pancasila and Civic Education subject, making learning more engaging, motivating, and student-centered.